How to give home BP monitoring patients the correct cuff: using BMI as a surrogate estimate of arm circumference. (14th October 2021) - Rison, S C G; Robson, J P
Abstract: Background: The key role of patient self-monitoring, already well established by large-scale forward planning initiative such the British National Health Service's (NHS) long-term plan, has been emphasised by the COVID19 pandemic. In the management of hypertension, much can be achieved through the provision of blood pressure monitors to patients, along with appropriate education and online blood pressure (BP) recording facilities. However, it is important to ensure that patients have the correct equipment to reliably measure their own blood pressures and to ensure they purchase or are supplied with validated monitors and, as undersized cuffs yield artefactually elevated BP readings, with correctly sized cuffs. Purpose: To demonstrate the use of Body Mass Index (BMI) as an estimate of Middle Upper Arm Circumference (MUAC) for purposes of blood pressure monitor cuff size requirement estimation and the application of this strategy to a national Home Blood Pressure Monitoring (HBPM) programme. Methods: The relationship between MUAC and BMI is well established; MUAC is used surrogate measure of BMI particularly in identifying underweight patients especially in environments where accurate recording of weight and height is challenging. Here, we reverse this relationship to use the BMI (one of the most commonly recorded datum in primary care patient records) to estimate patient MUACs. First, using manufacturer recommended cuff arm-circumference ranges and aggregate pre-established MUAC to BMI linear equations, we generate a simplified BMI to cuff-size scheme. Second, we apply this scheme to a UK Integrated Care System (a regional NHS organisation supporting 1.7 million adult patients in an English city) to estimate cuff requirement under NHS England's BPM@h HBPM initiative (in which patients with poorly controlled hypertension are allocated free home BP monitors). Lastly, we propose a patient-level tool for BP monitor cuff size prediction. Results: Our simplified scheme proposes the following cuff predictions: Small (S: 17–22cm): BMI <18kg/m 2 ; Medium (M: 22–32cm): BMI ≥18 and <28kg/m 2 ; Large (M: 32–42cm): BMI ≥28 and <38kg/m 2 and Extra-large (X: 42–50cm): BMI ≥38kg/m 2 . In our population of approximately 157, 000 adult hypertensive patients, 6, 039 were eligible for a BP monitor under the NHS England's BPM@h HBPM initiative. Using our simplified scheme, we predict cuff requirements as follows: S: 2%, M: 32%, L: 46%, X: 19%. Conclusion: Patient BMIs are a useful predictor of BP monitor cuff size requirement. They are readily available or calculatable from primary care records and their application to cuff size identification will improve accuracy of BP readings in HBPM initiatives. Our preliminary results suggest that the most commonly supplied "standard" cuff may be unsittable for well over 50% of patients and that extra-large cuff may be required for nearly 1 in 5 patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Barts CharityHealth Data Research UK